2013
DOI: 10.1186/1479-7364-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Update of the human and mouse SERPINgene superfamily

Abstract: The serpin family comprises a structurally similar, yet functionally diverse, set of proteins. Named originally for their function as serine proteinase inhibitors, many of its members are not inhibitors but rather chaperones, involved in storage, transport, and other roles. Serpins are found in genomes of all kingdoms, with 36 human protein-coding genes and five pseudogenes. The mouse has 60 Serpin functional genes, many of which are orthologous to human SERPIN genes and some of which have expanded into multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(184 citation statements)
references
References 78 publications
4
180
0
Order By: Relevance
“…Aox4 and SerpinA3i . Considering that SERPINA3 inhibits cathepsin G released by activated neutrophils (Heit et al, 2013), one can expect phenotypic immunological inference of SERPINA3 inactivation in the 101 reported 129 ESC-derived genetically modified mouse lines of which the targeted gene flanks the SerpinA3i locus. In an attempt to link the Aox4 passenger mutation to a phenotype observed in genetically modified congenic mice targeting an Aox4 -neighboring gene, we found that mice deficient in phospholipase Cε (PLCε) showed a similar thickening of the epidermis (Martins et al, 2014) as observed in Aox4 null mice (Terao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Aox4 and SerpinA3i . Considering that SERPINA3 inhibits cathepsin G released by activated neutrophils (Heit et al, 2013), one can expect phenotypic immunological inference of SERPINA3 inactivation in the 101 reported 129 ESC-derived genetically modified mouse lines of which the targeted gene flanks the SerpinA3i locus. In an attempt to link the Aox4 passenger mutation to a phenotype observed in genetically modified congenic mice targeting an Aox4 -neighboring gene, we found that mice deficient in phospholipase Cε (PLCε) showed a similar thickening of the epidermis (Martins et al, 2014) as observed in Aox4 null mice (Terao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…While this is the first report of a very large number of serpin transcripts from male ticks, data presented here are not unusual. High numbers of serpin sequences were reported in ticks I. scapularis (Mulenga et al, 2009), R. pulchellus (direct submission), and A. maculatum (Karim et al, 2011), in mosquitoes Anopheles gambiae, Culex quinquefasciatus , and Aedes aegypti (Rawlings et al, 2012), in Bombyx mori (Zou et al, 2009), Tribolium (Zou et al, 2007), Drosophila (Reichhart, 2005), in mouse and human genomes (Puente and López-Otín, 2004; Gatto et al, 2013; Heit et al, 2013), and in Arabidopsis and Oryza sativa (Fluhr et al, 2012). Such large serpin counts across a great diversity of taxa indicate the importance of this protein family in regulating homeostasis in most branches of life.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the severity of gluten immunopathology in NOD/DQ8 mice is influenced by the microbiota with which these mice are colonized and that administration of recombinant L. lactis expressing elafin can attenuate the inflammatory response of the host to gluten (12,23,24). Serpins are produced by a wide range of organisms and play a key role in maintaining immune homeostasis (25,26). In the gut, serpins are expressed at mucosal surfaces and are involved in regulating barrier function (27,28).…”
Section: Discussionmentioning
confidence: 99%